The Route to Health: China’s Belt and Road Initiative in COVID-19 Pandemic - I. I. Arsentyeva (Евразийская интеграция: экономика, право, политика)
This study examines the China’s Belt and Road Initiative in the context of the COVID-19 pandemic, which has created new parameters for building the world order, putting forward life and health as the main values.Aim. The study aims to analyze the Health Silk Road project as a Belt and Road’s important part which, according to the Chinese government’s statements, seeks to improve the health systems and health of the population of the participating countries.Tasks. The author traces the genesis of the Health Silk Road project; describes the main measures taken by China within the framework of this initiative since the spring of 2020; determines its significance for the PRC’s domestic and foreign policy; analyzes the main benefits and risks for the project participants.Methods. When working with scientific literature on the development of the Belt and Road Initiative under pandemic conditions, methods of critical and comparative analysis are applied. The author also analyzes the primary sources — statistical data, government documents, analytical materials, speeches by officials, papers of integration unions and international organizations, public opinion polls, etc.Results. The demand for humanitarian (medical) cooperation at the present stage is substantiated; the PRC’s “mask diplomacy” and its importance for domestic and foreign policy, including impact on the image of the State, are characterized; the opinions of Western experts are analyzed; the assessment of the Build Back Better World Initiative undertaken by G7 countries as a “democratic alternative” to the Chinese project is given.Conclusion. Based on the results of the study, it is concluded that the COVID-19 pandemic has demonstrated the flexibility of China’s policy, which was able to adapt to the unstable international situation, find new opportunities and development vectors, including the Health Silk Road, which is likely to remain a significant direction of the Belt and Road Initiative in a post-COVID-19 world.